Socioemotional Wealth and Innovativeness in Small‐ and Medium‐Sized Family Enterprises: A Configuration Approach. (5th January 2018) - Gast, Johanna; Filser, Matthias; Rigtering, J. P. Coen; Harms, Rainer; Kraus, Sascha; Chang, Man‐Ling
Abstract : What makes small‐ and medium‐sized family firms (family SMEs) innovative? Some family firm dynamics promote, yet others hinder innovation. It remains unclear whether combinations of family firm dynamics increase innovativeness. Our configurational perspective of socioemotional wealth (SEW) unravels determinants of family SMEs' innovativeness. We conduct a fuzzy set qualitative comparative analysis with 452 Swiss family SMEs. We categorize SEW dimensions into configurations of necessary and sufficient conditions. We contribute to theory on family SMEs' innovativeness because we reveal that the interplay of SEW dimensions leads to innovativeness. This offers practitioners a better framework to choose between SEW configurations.